The Impact of Social Isolation Due to COVID-19 on Symptom Progression in People With Dementia: Findings of the SOLITUDE Study - Manca, Riccardo; De Marco, Matteo; Colston, Amanda; Raymont, Vanessa; Amin, Jay; Davies, Rhys; Kumar, Pramod; Russell, Gregor; Blackburn, Daniel J.; Venneri, Annalena (Frontiers in Psychiatry, 2022)
Background: People with dementia (PWD) are vulnerable to abrupt changes to daily routines. The lockdown enforced on 23rd March 2020 in the UK to contain the expansion of the COVID-19 pandemic limited opportunities for PWD to access healthcare services and socialise. The SOLITUDE study explored the potential long-term effects of lockdown on PWD’s symptoms and carers’ burden. Methods: Forty-five carers and 36 PWD completed a telephone-based assessment at recruitment (T0) and after 3 (T1) and 6 months (T2). PWD completed measures validated for telephonic evaluations of cognition and depression. Carers completed questionnaires on their burden and on PWD’s health and answered a customised interview on symptom changes observed during the first months of lockdown. Longitudinal changes were investigated for all outcome variables with repeated-measures models. Additional post hoc multiple regression analyses were carried out to investigate whether several objective factors (e.g. demographics and time under social restrictions) and carer-reported symptom changes observed following lockdown before T0 were associated with all outcomes at T0. Results: No significant changes were observed in any outcomes over the 6 months of observations. However, post hoc analyses showed that the length of social isolation before T0 was negatively correlated with episodic and semantic memory performance at T0. Carers reporting worsening of neuropsychiatric symptoms and faster disease progression in PWD also reported higher burden. Moreover, carer-reported worsening of cognitive symptoms was associated with poorer semantic memory at T0. Conclusion: PWD’s symptoms and carers’ burden remained stable over 6 months of observation. However, the amount of time spent under social restrictions before T0 appears to have had a significant detrimental impact on cognitive performance of patients. In fact, carer-reported cognitive decline during social isolation was consistent with the finding of poorer semantic memory, a domain sensitive to progression in Alzheimer’s disease (AD). Therefore, the earlier stricter period of social isolation had a more detrimental impact on patients and their carers, followed by a plateau. Future interventions may be designed to maintain an optimal level of social and cognitive engagement for PWD in challenging times to prevent abrupt worsening of symptoms and associated detrimental consequences on patients’ families.